Rational and irrational vaccine hesitancy - Manfred S. Green (BMC, 2023)
Abstract In the paper published recently in this journal, Kumar et al. explained why the key to improved COVID-19 vaccine uptake is to understand societal reactions leading to vaccine hesitancy. They conclude that communications strategies should be tailored to the different phases of vaccine hesitancy. However, within the theoretical framework provided in their paper, vaccine hesitancy should be recognized as having both rational and irrational components. Rational vaccine hesitancy is a natural result of the inherent uncertainties in the potential impact of vaccines in controlling the pandemic. In general, irrational hesitancy is based on baseless information obtained from hearsay and deliberately false information. Risk communication should address both with transparent, evidence-based information. Rational concerns can be allayed by sharing the process in which dilemmas and uncertainties are dealt with by the health authorities. Messages on irrational concerns need to address head on the sources spreading unscientific and unsound information. In both cases, there is a need to develop risk communication that restores trust in the health authorities.